Faktor-Faktor Determinan Pemanfaatan E-Government oleh Masyarakat di Kota Probolinggo - Andre Firmansyah; Paulus Insap Santosa; Puguh Prasetya Utomo (Department of Government Studies, Universitas Syiah Kuala, 2023)
E-government implementation can facilitate public participation in terms of information disclosure, public services, as well as complaints and aspirations in formulating policies to achieve good governance. So it is necessary to analyze the determinant factors of e-government usage by citizens in th etechnical and social aspects. This research was conducted in the Probolinggo City, Indonesia as one of the cities that has implemented e-government system in public administration. This study uses evaluation models that integrates information system factors from the DeLone McLean model, social capital factors, and digital literacy factors. Data was collected through distributing questionnaires to respondents who have participated electronically with a sample of 210 people. This study uses quantitative methods with analytical techniques using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of this study indicate the influence of information system factors, social capital factors and digital literacy factors on use of e-government. As well as measuring the effect of citizen satisfaction and perceived usefullness on the continuance intention to use and recommend it. These results can be a new insight in implementing citizen-centered e-government to realize good governance